ANALISIS DISKRIMINAN OPERATOR SELULER TELKOMSEL DAN OPERATOR SELULER LAINNYA (INDOSAT OOREDOO, XL AXIATA, 3) TERHADAP KEPUTUSAN BRAND SWITCHING DI STIE DEWANTARA - Osta Nababan, Benny; Ambiatul Awwalin, Irhaz (Economicus, 2019)
The purpose of this study was to compare the independent variables of Telkomsel cellular operators with other operators and determine the discriminant model of the brand switching of cellular operators Telkomsel. The approach used in this study is a comparative quantitative method. Independent variable consisting of product quality (X1), price (X2), promotion (X3) and brand image (X4), the dependent variable is Brand Switching (Y). The population of this study was 1028 STIE Dewantara (Odd Year 2015-2018) students. The number of samples taken was 100 samples with Slovin formula with alpha 5%. Data analysis using discriminant analysis. The results showed that the variables used in this study were overall valid and reliable so that the data obtained could be used in discriminant analysis of cellular operators of Telkomsel and other cellular operators. The value of consumer satisfaction of cellular operators is, on average, more satisfied to Telkomsel cellular operators, which is shown by the average value of satisfaction of 397.07 points while other cellular operators amount to 357.87 points. There are 3 differences in consumer perceptions of cellular operators towards Telkomsel. The difference in perception is in the variables of product quality, promotion and brand image. This means that users of cellular operators will compare these 3 variables before making a move to the Telkomsel brand.